Pengaruh Endorphine Massage Terhadap Kualitas Tidur Ibu Hamil Usia Kehamilan 37- 40 Minggu - Unida, Anya; Dwi Estuning Rahayu; Susanti Pratamaningtyas (JURNAL KEBIDANAN, 2024)
The decrease sleep duration during pregnancy increases in the third trimester. Giving non-pharmacological therapies that can be done to help improve sleep quality is to do an endorphine massage. The aim of this study was to determine the effect of endorphine massage on the sleep quality of pregnant women 37-40 weeks in the Working Area of the Mojo Health Center, Kediri Regency. The method of this research is Pre-Experiment with One Group Pretest-Posttest Design without a control group, using a total sampling technique with a total sample of 30 respondents. Endorphine massage intervention will be carried out 2 times in a row with the duration of 15-20 minutes each session. Data collection used the questionnaire PSQI, analysis used Mc Nemar test obtained P-Value 1 > 0.05, it can be concluded that statistically, there is no effect of endorphine massage on the sleep quality of pregnant women 37-40 weeks in the Working Area of the Mojo Health Center, Kediri Regency. Poor sleep quality in pregnant women due to frequent awakening from sleep. This makes it difficult for pregnant women to achieve deep sleep. So it is necessary to do endorphine massage regularly by paying attention to disturbing factors, so that pregnant women can experience better quality sleep.